Efektivitas Layanan Gadai Syariah Pegadaian dalam Meningkatkan Akses Pembiayaan UMKM: Studi Literarur - Nurintan Nurintan; Malika Kesya Aulia; Hasniar Hasniar; Anggun Ade Fatrisia; Amanda Hirmayani; Herni Herni (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting national economic growth but continue to face challenges in accessing business financing. Pegadaian Syariah, as an Islamic financial institution, provides financing services based on the rahn contract as a fast, simple, and Sharia-compliant financing alternative. This study aims to analyze the effectiveness of Pegadaian Syariah's pawn services in improving MSMEs' access to financing through a literature review. The research employed a descriptive qualitative approach using the literature review method. Secondary data were collected from scientific journals, books, regulations, and DSN-MUI fatwas and analyzed using content analysis. The findings indicate that Pegadaian Syariah's pawn services effectively improve MSMEs' access to financing through simple procedures, easy requirements, rapid fund disbursement, and the implementation of Sharia principles. Financing products such as Rahn, Arrum, and Rahn Tasjily contribute to increasing business capital and supporting the sustainability of MSMEs. However, the effectiveness of these services is still influenced by limited Islamic financial literacy, inadequate collateral, and insufficient product promotion. Therefore, strengthening financial literacy, expanding service accessibility, and developing innovative financing products are essential to enhance the contribution of Pegadaian Syariah in supporting the growth and sustainability of MSMEs.